PENGEMBANGAN BAHAN AJAR BERBASIS PENELITIAN KARAKTERISASI PROTEIN MEMBRAN SPERMA PADA MATAKULIAH BIOTEKNOLOGI - Oktaviana, Ika; B Sumitro, Sutiman; Lestari, Umie (Jurnal Florea, 2015)
The purpose of the research and development is to produce teaching materials such as textbookssupporting course in Biotechnology research based on the characterization of the sperm membraneproteins for students who take a course in Biotechnology. This research is a research and development, where the results of research become the teaching materials developed supporting Biotechnologycourse. Development models have prepared using ADDIE Model. Sources of data in this researchinclude laboratory research and validation of the results sheet of Biotechnology material experts,instructional design experts, the media, and the trials in students. The analysis is used descriptiveanalysis and quantitative descriptive exploratory. The results of the research have developed becometeaching materials like text books supporting courses and have been validated by the Biotechnology,the biotechnology material experts, instructional design experts, the media, the individual testing, andgroup trials. Based on the results of the validation material have obtained value of 89.56%, the resultsof the design validation and media experts to get the value of 93.75%, it means that the teachingmaterials has been developed which suitable to be used as a teaching material support biotechnologycourse. While the experiments performed to get a data the percentage of students that are equal to88.98% and included in the category of âvery goodâ, but still need to be revised based on advices andcomments from students.Keywords: Teaching material, Characterization of Membrane Proteins, Biotechnology.Â